2022
DOI: 10.3389/fpls.2022.900939
|View full text |Cite
|
Sign up to set email alerts
|

Control Efficacy and Deposition Characteristics of an Unmanned Aerial Spray System Low-Volume Application on Corn Fall Armyworm Spodoptera frugiperda

Abstract: As a major global pest, fall armyworm (FAW), Spodoptera frugiperda, invaded China in 2019, which has seriously threatened the safety of China's food production and raised widespread concerns. As a new low-volume application technology, an unmanned aerial spray system (UASS) is playing an important role in the control of FAW in China. However, the studies on the effect of the water application volume on the efficacy of FAW using UASS have been limited. In this study, Kromekote® cards were used to sample the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(58 reference statements)
2
16
0
Order By: Relevance
“…This reveals significant potential for improving the uniformity of pesticide deposition distribution applied by UASS. These findings align with prior research, demonstrating that the CV of UASS can exceed 40%, even reaching 100%–120% for both single and multiple swaths 46–48 . Variability in pesticide deposition distribution is a common occurrence in field applications due to the unique characteristics of these systems.…”
Section: Resultssupporting
confidence: 89%
“…This reveals significant potential for improving the uniformity of pesticide deposition distribution applied by UASS. These findings align with prior research, demonstrating that the CV of UASS can exceed 40%, even reaching 100%–120% for both single and multiple swaths 46–48 . Variability in pesticide deposition distribution is a common occurrence in field applications due to the unique characteristics of these systems.…”
Section: Resultssupporting
confidence: 89%
“…From Figs 3 and 4, the CV values of the six‐rotor UASS sprayer within a single swath (48.0–83.4%) were observed to be much higher than values for conventional boom sprayers, indicating a poor distribution uniformity measured at the top of the artificial rice plants. These results are in line with those of previous studies, which have shown that the CV values of UASS were almost above 40% and even reached 100–120%, for both a single swath and multiple widths 18,20,42–46 . This is a common phenomenon in current UASS field application operations in China, determined by the characteristics of the UASS itself.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with those of previous studies, which have shown that the CV values of UASS were almost above 40% and even reached 100-120%, for both a single swath and multiple widths. 18,20,[42][43][44][45][46] This is a common phenomenon in current UASS field application operations in China, determined by the characteristics of the UASS itself. Unmanned aerial sprayers normally use ultra-low volume (ULV) and very-low volume (VLV) applications, and the fine droplets are greatly influenced by rotor airflow and external natural wind.…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the fact that during the applications, the so-called "umbrella effect" occurred, in which the leaves in the upper and middle layers prevented the increase in coverage, density, and deposition of drops in the lower layer and fruit clusters. The authors of [46], using a UAV equipped with the XR110-01 and -015 nozzles, to control the caterpillar (Spodoptera frugiperda) on corn plants, observed that coverage and droplet deposition were higher in the upper layer and lower in the lower layer. Other studies support this statement using UAV-applied flat-fan nozzles, such as on citrus [47] and on pigeon pea [48].…”
Section: Discussionmentioning
confidence: 99%